115 Sexual Assessment in Breast Cancer Survivors Receiving Aromatase Inhibitors: Are They Interested on Sexology Consultation?. (1st May 2022) - Anglès-Acedo, S; Ribera-Torres, L; Mension, E; Gómez Carballo, S; Tortajada, M; Matas, I; Alonso, I; Castelo-Branco, C
ABSTRACT: Introduction: Sexuality complaints are common among breast cancer (BC) survivors mostly related to diagnosis and treatment. Aromatase inhibitors (AI) are a well-known cause of severe genitourinary syndrome of menopause (GSM) and dyspareunia. It is noteworthy that to evaluate sexual function a proper evaluation of both the past and current sexuality is needed. Objective: baseline assessment of BC survivors receiving AI with GSM and dyspareunia who attend a sexology consultation. Methods: Observational cross-sectional descriptive data from an ongoing RCT study (NCT04619485) focused on baseline sexual records of BC survivors receiving AI with GSM and dyspareunia, aimed to better understand the sexual life of the participants before any treatment. Women received an hour sexual counselling based on the PLISSIT model (permission, limited information, specific suggestion and intensive therapy). According to DSM 5, sexual disorder should be considered when there is clinically significant disturbance. We ask patients to fill in a visual analogue scale (VAS) 0-10 about disturbance by their sexual life and classified disturbance as clinically significant when women scored >3. Dyspareunia intensity is also assessed in all patients (sexually active and inactive) according to their last coital sexual activities. Both their past and current sexual life are evaluated. Results: We included 73 women until June 2021. On average, patients had been diagnosed of BC 5 years ago and had been treated with surgery (98.6%), radiotherapy (73.2%), chemotherapy (81.1%) and hormonal therapy (100%). Sexual activity rate was 63%. Table 1 describes the characteristics of the sample, classified according to their sexual activity and to whether they attended or not the sexual assessment visit. Sexually inactive women are older and have more intense dyspareunia than their sexually active peers, being such differences statistically significant. 19 women rejected sexual counselling due to shame, personal beliefs or lack of motivation on the topic. No statistically significant differences were found between this collective and women who wanted sexual assessment. All women who attended baseline sexual visit (N=54) were heterosexual but one bisexual. 76.5% of them reported a stable relationship whereas 23.5% were unpartnered. Among sexually active women who attended baseline sexual visit (N=37, 68.5%), 23.5% reported solo sex, 35.3% reported partnered sex and 41.2% both sexual conducts. According to the kind of sexual activity, 77% of all women had vaginal sex and external conducts, 20% only external conducts and 3% only vaginal sex. Regarding the sexuality of the 54 evaluated women, 80.4% had a preserved and satisfactory sexual life with orgasms previous to BC diagnosis. Most of the patients (62.7%) reported worsening of their sexual life after AI treatment whereas only 17.7% maintained their good sexual life. All women with previous sexual dysfunction (19.6%) maintained their symptoms. Conclusions: three out of four patients suffering from BC are interested in an evaluation of their sexuality. Most of them show a sexuality impairment at the baseline visit. This information should be considered when planning the holistic approach to patient care by a multidisciplinary team, especially when there is an aim to treat a sexual symptom.